Estudio de pre-factibilidad del proyecto hidroeléctrico caluma alto - Montalvo, G. (2009)
The pre-factibility study of Caluma Alto Hydroelectric Project comes such as a short period solution of the energetic necessities in different regions of the country. The study consist in the construction of one central hydroelectric, taking approach of the rivers, Tablas and Escaleras (625 m.s.n.m.) This will be discharged in the machine house situated in the (525 m.s.n.m.) which will have 5.73MW of Potency. Furthermore, the obtained energy will be sent to the National Interconnected system, this construction will take care of ambient and near population, obtaining a minimal impact of it and it will follow the necessary ambient norms.